Answer :

x2y (3 – 2x2y) – 1 (3 – 2x2y)

= 3x2y- 2x4y2 – 3 + 2x2y


= 2x4y2 + 5x2y – 3


Putting x = -1 and y = -2, we have


= [(-1)2 (-2) – 1] [3 – 2 (-1)2 (-2) = [-2 (-1)4 (-2)2 + 5 (-1)2 (2) – 3]


= (-2 – 1) (3 + 4) = - 8 – 10 – 3


-21 = - 21


Therefore,


L.H.S = R.H.S


Hence, verified


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Multiply the follNCERT - Mathematics Exemplar

Simplify

<
NCERT - Mathematics Exemplar

Find the followinRD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Multiply:

RD Sharma - Mathematics